The Constitutionality of State Authority Over Water Resources Management Based on Human Rights Principles - Ricko Anas Extrada; Kamarusdiana Kamarusdiana (UIN JAKARTA, 2021)
This study intends to investigate the contrast between the private sector's implementation of water privatization in Indonesia and the state's responsibility for managing water resources in light of human rights standards. In accordance with the mandate of the constitution, which states in Article 33, paragraph 3, that